Hypusine Plays a Role in the Translation of Short mRNAs and Mediates the Polyamine and Autophagy Pathways in Saccharomyces Cerevisiae - Paiva, Ana Carolina Silva; Demarqui, Fernanda Manaia; Santoni, Mariana Marchi; Valentini, Sandro Roberto; Zanelli, Cleslei Fernando (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2021)
The cell highly regulates the translational process aiming to maintain cellular stability and viability for mechanisms at the transcriptional, translational, or metabolic level, such as the control of transcripts forwarded for translation or autophagy. The translation elongation factor 5A (eIF5A) is evolutionarily conserved and essential in eukaryotic cells. eIF5A undergoes a post-translational modification, called hypusination, which has two enzymatic steps. The first stage, catalyzed by the deoxyhypusine synthase, occurs in a spermidine-dependent manner. Spermidine is a polyamine in which intracellular imbalance can affect some cellular processes. Studies show that this modification is fundamental to the role of eIF5A in the cell, assisting in the translation of a subset of mRNA. We analyzed transcriptional and translational profiles of the deoxyhypusine synthase mutant (dys1-1) in Saccharomyces cerevisiae. From Polysome-seq, our results showed that the lack of hypusination leads to the impairment on the translation of short ORFs, that code ribosomal mitochondrial proteins. From both profiles, the expression of genes and transcription factors of the polyamine pathway, which needs strict cell control, was altered. Besides, the inhibition of hypusination by GC7 showed an increase in the protein level of two autophagy proteins, Atg1 and Atg33, the latter is specific to mitophagy. In response to the metabolic problems caused by non-hypusination, the cell can respond with mitophagy and macroautophagy to maintain cell stability.